The relevance of Baayun Maulid values as learning resources on Social Studies - Handy, Muhammad Rezky Noor; Abbas, Ersis Warmansyah; Mutiani, Mutiani; Jumriani, Jumriani; Putra, Muhammad Adhitya Hidayat; Rusmaniah, Rusmaniah; Ilhami, M. Ridha; Maulidah, Dina (Universitas Negeri Yogyakarta, 2024)
The Implementation of religious values-based traditions is inherent in the Banjar community. The Banjar people commemorate the Prophet Muhammad SAW's birthday by swinging a child or adult called Baayun Maulid. This article aims to describe the value of Baayun Maulid as a source of social studies learning. Approach qualitative and descriptive methods were used in the study. Three stages of data collection, among others; observation, interview, and documentation. Data sources were taken from informants directly involved during the implementation, namely community leaders, documentation in pictures, and recordings. Data were analyzed through data reduction, data presentation, and verification. The validity of the data through the triangulation of sources and techniques. The study results describe the relevance of Baayun Maulid, starting by providing an analysis of the sub-learning materials and research findings. Based on the textbook's e material results, the religious costs and the value of cooperation can be included in the Social Studies material for class VII, the subject matter of Cultural and Ethnic Diversity, the sub-discussion of Traditional Ceremony, Besides that, it also uses various learning media such as photos, videos and learning management systems that support learning with technology so that the Baayun Maulid religious ritual activities are not only ritualistic but are able to develop the character of students on the class and the teacher using LMS composing them with other learning media such as photos, videos and others.